ROALD DAHL'S INGENIOUS LANGUAGE PLAY IN THE USE OF FIGURATIVE LANGUAGE - Trisnowati Tanto (International Journal of Humanity Studies (IJHS), 2020)
Roald Dahl is widely known for being one of the most creative writers, both in the ideas of the stories and the language use. His use of language is exceptional and tends to show some playfulness which makes the writing even more attractive. This play on language is in fact considered his writing style. What is worth noticing further is that playfulness can also be seen in the use of figurative language. This paper specifically focuses on the figurative language such as similes, metaphors, and personification in Dahls novels for children: The BFG, Charlie and the Great Glass Elevator, and The Witches. Since this paper reveals Dahls use of language play as his writing style, it belongs to Stylistics, the study of style. The paper uses a descriptive qualitative method. The data of similes and personification are collected and then analysed in terms of how they show the ingenious side of the writer in using language. The findings show that the figurative language used in the novels indeed makes optimal use of sound play and wordplay. Besides, the figurative language is also closely associated with the fact that the novels are intended for children.